Analiza lingwistyczna komunikacji wyborczej Partii Sługa Narodu w czasie wyborów samorządowych we Lwowie w 2020 / A Linguistic Analysis of Electional Communication of the Nation’s Servanthood Party during the Local Government Election in Lviv, in 2020 - Liubomyr Skochylias; Jurij Hajduk (Language, Culture, Politics)
The article, following the course of the 2020 local government election in the Lvov Region, presents a linguistic analysis of the electoral communication of the Nation’s Servanthood Party. The research was based on the methodology practiced by political linguistics. The results of the analysis allow to conclude that during the electoral communication the discussed here party took advantage of a wide spectrum of techniques and political language repertoire. During the period of electoral communication, the following strategies were used: consolidation (policy of the Ukrainian nation integration), auto-presentation (demonstration of professionalism, patriotism, responsibility), and argumentation (tactics of assumption validity, dialog, compromise).